Macroeconomics determinants of external debt in Malaysia / Nur Aina Adila Saharuddin - Saharuddin, Nur Ana Adila (2018)
Malaysia has shown an increasing model of total outstanding external debt and as a small economy that formulates and implements a prudent debt management policy. Besides that, external debt needs to be allocated to domestic investment, in return, make economic growth in the long run and implying that Malaysia's external debt position sustainable. However, external debt has been benefits to economic growth and also can improve the potential of servicing the debt without crowding out the country in investment. This paper aims to study the selected macroeconomics determinants of external debt in Malaysia This study will be used external debt in Malaysia dependent variable and gross domestic product, interest rate, inflation and money and quasi money (M2). This paper seeks to examine the selected macroeconomics determinants of external debt in Malaysia for the time period of 1987-2016. This study used the unit root test, descriptive analysis, normality test, autocorrelation test, heteroskedasticity, functional form, multicollinearity and Durbin Watson. The result shows that variables have positive and negative relationship towards external debt in Malaysia.